POLA PEMBINAAN TAHSIN ALQURAN DI KALANGAN MAHASISWA: (Analisis Pola Pembinaan pada Himpunan Qari Qariah Mahasiswa Sulawesi Tengah (HIQMAH) - Tamrin Tamrin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2016)
This paper describes the pattern formation of Tahsin Qur'an organized by the student Association HIQMAH as an institution that bring together people who have a talent and interest in the art of reading and writing the Qur'an. The description was -analytic descriptive study, with a focus on the activities undertaken tahsin Qur'an start from the recruitment process to the implementation of various scientific studies both of scientific seminars or meeting. It can be concluded that the Qari and Qariah of Student Association (HIQMA) Central Sulawesi carry out its activities in the form of regular coaching per week, their participation in the Musabaqah event until taklim program in accordance with programs determined in the meeting program. Qur'an recitations art that developed in the Islamic countries and Tahfidz Qur'an is very major activities that can be especially developing capabilities as well as the deepening of the sciences of the Qur'an and recitation for students.